Transformation and Challenges of Digital Journalism in Aceh - Fauzi Fauzi; Marhamah Marhamah; Shafira Ulfa Rahmani (Komunikator, 2023)
Technological developments have changed the distribution pattern and access to information from conventional to digital media. Hence, digital journalism has an impact on the media industry and journalists. The purpose of this research is to analyze the transformation and challenges of digital journalism from the perspective of journalists in Aceh. This research uses a desciptive qualitative approach. Interviews were conducted with ten journalists in Aceh from print, radio, television, and online media. Validity of the data was tested using the technique of triangulation of sources and data analysis of the Miles and Huberman models, namely data reduction, presentation, and verification. The results of journalism platform research in the digital era adapt to media convergence. The journalism format incorporates text, video, and images. The challenge is maintaining the quality of journalism, both credibility, and accuracy. Journalists must improve their abilities and skills in using digital technology in order to survive.